2011
DOI: 10.1111/j.1365-294x.2011.05206.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytonuclear evidence for hybridogenetic reproduction in natural populations of the Australian carp gudgeon (Hypseleotris: Eleotridae)

Abstract: Although most vertebrates reproduce sexually, a small number of fishes, amphibians and reptiles are known in which reproduction is asexual, i.e. without meiotic recombination. In fishes, these so-called unisexual lineages usually comprise only females and utilize co-occurring males of a related sexual species to reproduce via gynogenesis or hybridogenesis. Here, we examine patterns of microsatellite and mitochondrial DNA (mtDNA) variation in a widespread group of freshwater fishes (carp gudgeons; Hypseleotris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 56 publications
(86 reference statements)
5
88
0
Order By: Relevance
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009). Significantly, these rare unisexual animals are largely associated with polyploidy origin (Neaves and Baumann, 2011;Otto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009). Significantly, these rare unisexual animals are largely associated with polyploidy origin (Neaves and Baumann, 2011;Otto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of the lineages consists almost exclusively of males, suggesting some form of asexual reproduction by males [17]. Detailed analyses of genotypes suggest that the male lineage most likely reproduces via hybridogenesis [17,27].…”
Section: (E) Carp Gudgeons Of the Genus Hypseleotrismentioning
confidence: 99%
“…There are three distinct, co-occurring carp gudgeon lineages in the Murray River in South Australia [17,27]. One of the lineages consists almost exclusively of males, suggesting some form of asexual reproduction by males [17].…”
Section: (E) Carp Gudgeons Of the Genus Hypseleotrismentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, taxonomical difficulties in species identification combined with extensive hybridization (Bertozzi et al, 2000;Schmidt et al, 2011) have resulted in the MDB carp gudgeons to be referred to either as western carp gudgeon (in the broad sense) or as a species complex Hypseleotris spp., otherwise known as 'carp gudgeon group' (Humphries et al, 1999;King et al, 2003;Vilizzi, 2012). Across the MDB, Hypseleotris spp.…”
Section: Introductionmentioning
confidence: 99%